Download presentation

Presentation is loading. Please wait.

Published byTrevor Short Modified over 7 years ago

1
Solving a System of Equations by ELIMINATION

2
Elimination Solving systems by Elimination: 1.Line up like terms in standard form x + y = # (you may have to use inverse operations) 2.Look at coefficients for something to cancel / eliminate (you may have to multiply) 3.Add equations together 4. Solve for the remaining variable. 5. Substitute back into original equation

3
-2(3x + 2y = -6) -6x – 4x = 12 3(2x + 5y = 7) 6x + 15y = 21 11y = 33 y = 3 3x + 2y = -6 2x + 5y = 7 3x + 2(3) = -6 3x + 6 = -6 -6 -6 3x = -12 3 x = -4 The solution to the system is (-4,3)

4
4x + 3y = 5 2x – 3y = 7 Line up like terms (you may have to use inverse operations) Look for something to cancel (you may have to multiply) Add equations together Substitute back into original equation Check!

5
2x + y = 9 -x + 4y = 0

6
6x – 3y = -3 -12x + 3y = -3

7
3x – 3y = -15 -4x + 2y = 4

8
x + y = 2 x – y =0

9
Review What are the steps for solving a system of equations by elimination?

Similar presentations

© 2022 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google